2020
DOI: 10.3390/en13143734
|View full text |Cite
|
Sign up to set email alerts
|

1D Simulation and Experimental Analysis on the Effects of the Injection Parameters in Methane–Diesel Dual-Fuel Combustion

Abstract: Notwithstanding the policies that move towards electrified powertrains, the transportation sector mainly employs internal combustion engines as the primary propulsion system. In this regard, for medium- to heavy-duty applications, as well as for on- and off-road applications, diesel engines are preferred because of the better efficiency, lower CO2, and greater robustness compared to spark-ignition engines. Due to its use at a large scale, the internal combustion engines as a source of energy depletion and poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The next step would be to measure the engine airflow in order to assess the fuel/air ratio that guarantees the best performances and evaluate it at different electrical power outputs as well as analyze the in-cylinder pressure for a better understanding of the combustion process [45].…”
Section: Discussionmentioning
confidence: 99%
“…The next step would be to measure the engine airflow in order to assess the fuel/air ratio that guarantees the best performances and evaluate it at different electrical power outputs as well as analyze the in-cylinder pressure for a better understanding of the combustion process [45].…”
Section: Discussionmentioning
confidence: 99%
“…After multiple machining processes, the surface of sliding bearing pair cannot be completely smooth and the dynamic pressure oil film thickness is so small under heavy load conditions and even reaches the order of roughness (several microns), that the rough contact of rough surface cannot be ignored. The contact pressure between rough peaks can be calculated by Greenwood/Tripp model [8]: The comparison of viscosity temperature relationship between SAE 15W40 and SAE 0W20 standard oil depicts in Figure 5, using data from the standard oil database in AVL Excite software.…”
Section: Rough Contact Modelmentioning
confidence: 99%
“…Since most of the friction losses in the ICE occur at the cylinder inner surface with piston and piston ring mating and crankshaft bearing friction, the exploration of friction reduction for these sliding friction pairs is mainly in the areas of lubrication additives, application of advanced coating and surface technologies, precise lubrication theory and simulation techniques. Other works performed an overview of the combustion technologies that have been tested able to improve the CO 2 and the NOx-Soot trade-offs such as specific bowl design, innovative fuel injection systems [7][8][9][10] and clean combustion technologies [11,12]. Studies have shown that reducing oil viscosity can be effective in improving fuel efficiency, but the problem that accompanies the application of lower viscosity oils is the accentuation of wear problems caused by the inadequate lubrication carrying capacity of lower viscosity oils [13].…”
Section: Introductionmentioning
confidence: 99%
“…Multiparameter research results on methane and diesel fuel combustion were analyzed in [8]. In that paper, the effects of the premixed ratio, injection pressure, and fuel doses in relation to the engine efficiency were assessed.…”
Section: Introductionmentioning
confidence: 99%